Iqbal’s ego philosophy and its importance in awakening man’s religiosity - Abdul Razak, Mohd Abbas (2012)
History reveals the fact that the coming of modernity and secularism has allured modern man towards a materialistic concept of life at the expense of neglecting his spiritual needs and role as the vicegerent of God. This predicament has not only marred man’s relationship with God but has also failed man from understanding his true nature and mission in life. The consequences of people not living the ideal religious life regardless of being in the East or West, have lately witnessed the erosion of human and spiritual values, severe degradation of the environment, racism, terrorism, outbreak of wars, poor state of mental health and a whole lot of other psychopathological illnesses. In view of these human conditions, this philosophical paper intends to explore and draw out conclusions from the philosophical thoughts of Muhammad Iqbal (1877-1938) with regards to his ego philosophy that explains the relationship between man, God and the universe. The lessons drawn out from Iqbal’s ideas can be of great use in awakening man’s religiosity towards God and improving his quality of life by striking a harmonious relationship with God, environment and fellow human beings.